A study on sustainability analysis of solid oxide fuel cell and proton exchange membrane electrolyzer integrated hybrid multi-generation system. (22nd July 2022) - Inac, Selcuk; Unverdi, Salih Ozen; Midilli, Adnan
Abstract: The main objective of this study is to perform the sustainability analysis of a proton exchange membrane electrolyzer (PEME) and solid oxide fuel cell (SOFC) integrated hybrid multi-generation system that is designed to operate in four modes. In this regard, the effects of performance parameters of PEME and SOFC systems on the sustainability of hybrid multi-generation system are parametrically investigated. Accordingly, in terms of hydrogen production, the best value of hydrogen production is estimated to be 33.09 kg/h for both M1 and M2 operating modes. Moreover, in terms of the sustainability indicators, the maximum power generation of the system is calculated to be 13.9 MW while maximum energy and exergy efficiencies and exergetic sustainability index are respectively obtained to be 89%, 47% and 0.85 in M3 operating mode. However, minimum total product cost per unit energy generation is estimated to be 15.64 /GJ in M1 operating mode. Furthermore, in terms of the exergetic sustainability index, the maximum effect ratios of the SOFC and PEME on the hybrid multi-generation system are respectively determined to be 5.076 and 16.124 in M1 operating mode. Highlights: PEME and SOFC are important subsystems for a hybrid multi-generation system. Sustainability analysis of the system indicates the applicability of multi-generation system. Operation modes of integrated system are important for continuous operation. Maximum exergy efficiency and exergetic sustainability index are obtained as 47% and 0.85, respectively, in M3 operating mode. Minimum environmental effect factor is calculated as 1.17 in M3 operating mode.